Pengaruh Literasi Investasi Syariah, Promosi Produk dan Kemudahan Akses terhadap Minat Investasi Tabungan Emas Melalui Lembaga Keuangan Syariah : Studi Kasus Masyarakat Kota Pematang Siantar - Febriansyah, Andrian; Ikhsan Harahap, M; Lathief Ilhamy Nasution, M (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The growth of sharia-based gold savings investment in Indonesia is growing along with the digitalization of financial services, but public interest in investing is not optimal due to low levels of sharia investment literacy, the effectiveness of product promotions, and service accessibility. The purpose of this study is to examine how the interest of Pematangsiantar City residents in investing in gold savings through sharia financial institutions is influenced by sharia investment literacy, product advertising, and accessibility. This study uses an associative research design and quantitative methodology. Purposive sampling was used to select 100 respondents as the research sample. The criteria for respondents were that they must be at least 17 years old and have previously invested in gold savings through sharia financial institutions. SmartPLS 4 was used to analyze the data using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach. The results show that interest in investing in gold savings is positively and significantly influenced by sharia investment knowledge, product advertising, and accessibility. These three variables explained 77.9% of the variance in investment interest, according to a coefficient of determination (R²) of 0.779, with additional factors outside the research model influencing the remaining portion. These results suggest that to increase public interest in investing in Islamic gold savings, promotional techniques need to be strengthened, Islamic investment education needs to be improved, and easily accessible digital services need to be provided.